The Inbetweeners: Standardizing Juvenileness and Recognizing Emerging Adulthood for Sentencing Purposes After Miller - Kevin J. Holt (Washington University Law Review, 2015)
In June 2012, the United States Supreme Court decided Miller v. Alabama, marking significant progress in the Court’s Eighth Amendment jurisprudence regarding juvenile offenders. In Miller, the Court held mandatory life without parole for juvenile offenders to be unconstitutional. Following its reasoning set forth in previous cases, the Court found that “children are different” in a fundamental way: offenders under the age of eighteen are incapable of being criminally liable to the same extent as their adult counterparts. Miller was an enormous win for the juvenile justice system, because it meant that the Court concluded that, as a constitutional rule, juveniles’ cognitive development has not progressed enough to warrant adult sentencing (save for extreme circumstances, which the Court did not outline). Although that conclusion has major implications for juvenile justice, some questions remain. After Miller, there are two related, unsettled issues that contribute to the daunting uncertainty facing juvenile offenders. First, there is no uniform definition or cutoff of the “juvenile” class of defendants in the United States, which means due process may differ from state to state, depriving some children of the full constitutional protection intended by the Court. The Court’s decision in Miller may necessitate a constitutional definition of “juvenile” as a person under eighteen years old. Second, if the neurological research and social science on which Miller was based conclude that cognitive abilities are not fully developed until around age twenty-five, it may be arbitrary and inconsistent to choose age eighteen as the age after which a defendant may be subject to mandatory life without parole, or even the death penalty. The distinction of adulthood beginning at age eighteen is arguably based on no more than traditional and outdated norms. The Court’s Eighth Amendment jurisprudence and cognitive science articulated in Miller and its forebears may necessitate legal recognition of a stage of life between adolescence and adulthood often called “emerging adulthood,” during which defendants should be entitled to further special consideration under the Eighth Amendment. This Note examines the Supreme Court’s Eighth Amendment jurisprudence in relation to juvenile sentencing, and the social science, psychology, and neuroscience research underpinning the Court’s decisions in these cases. In short, this Note offers two proposals. First, there should be a uniform definition of “juvenile” that ends at eighteen years of age, and this should be the cutoff age for juvenile court jurisdiction nationwide. Second, courts should recognize an age group between the ages of eighteen and twenty-five, called “emerging adulthood,” during which judges would potentially consider a defendant’s youthful characteristics, capacity for change, and culpability in deciding whether to give the defendant a sentence as harsh as his or her fully formed adult counterparts.
Keywords: Juvenile Law; Juvenile justice; Miller; Miller v. Alabama; Miller resentencing; Juvenile offenders